New Properties of a Bioinspired Pyridine Benzimidazole Compound as a Novel Differential Staining Agent for Endoplasmic Reticulum and Golgi Apparatus in Fluorescence Live Cell Imaging - Llancalahuen, Felipe M.; Fuentes, Juan A.; Carreño, Alexander; Zúñiga, César; Páez-Hernández, Dayán; Gacitúa, Manuel; Polanco, Rubén; Preite, Marcelo D.; Arratia-Pérez, Ramiro; Otero, Carolina (Frontiers in Chemistry, 2018)
ABSTRACT In this study, we explored new properties of the bioinspired pyridine benzimidazole compound B2 (2,4-di-tert-butyl-6-(3H-imidazo[4,5-c]pyridine-2-yl)phenol) regarding its potential use as a differential biomarker. For that, we performed 1D 1HNMR (TOCSY), UV-Vis absorption spectra in different organic solvents, voltammetry profile (including a scan-rate study), and TD-DFT calculations that including NBO analyses, to provide valuable information about B2 structure and luminescence. In our study, we found that the B2 structure is highly stable, where the presence of an intramolecular hydrogen bond (IHB) seems to have a crucial role in the stability of luminescence, and its emission can be assigned as fluorescence. In fact, we found that the relatively large Stokes Shift observed for B2 (around 175 nm) may be attributed to the stability of the B2 geometry and the strength of its IHB. On the other hand, we determined that B2 is biocompatible by cytotoxicity experiments in an epithelial cell line. Furthermore, in cellular assays we found that B2 could be internalized by passive diffusion in absence of artificial permeabilization at short incubation times (15 min to 30 min). Fluorescence microscopy studies confirmed that B2 accumulates in the endoplasmic reticulum (ER) and Golgi apparatus, two organelles involved in the secretory pathway. Finally, we determined that B2 exhibited no noticeable blinking or bleaching after 1 h of continuous exposure. Thus, B2 provides a biocompatible, rapid, simple, and efficient way to fluorescently label particular organelles, producing similar results to that obtained with other well-established but more complex methods.